A rapid method of grading cataract in epidemiological studies and eye surveys. Issue 11 (November 1988) - Mehra, V; Minassian, D C
Abstract : A rapid method of grading clinically important central lens opacities has been developed for use in eye surveys and in epidemiological studies of cataract and has been field-tested in a specifically designed observer agreement study in a survey of a rural community in Central India. The grading method is based on simple measurement of the area of lens opacity that obscures the red reflex relative to the area of clear red reflex, as visualised through the undilated normal pupil. Good to almost perfect agreements were attained between two ophthalmologists and two trained ophthalmic assistants for overall grades of central lens opacity. Most disagreements were trivial in nature and were concerned with difficulties in distinguishing grade 0 from grade 1, and with hazy appearance of the red reflex in high myopes and in cases of early nuclear sclerosis. Teaching materials including video tape and slides for training survey teams and other workers are in preparation.